Experimental Study on 3D Roughness and Shear Failure Mechanism of Rock Mass Discontinuity. (1st April 2018) - Wei, Jihong; Men, Yan; Sun, Shaorui; Le, Huilin; Zhu, Feng
Abstract : A set of systematic experimental methods, including 3D accuracy scanning and identification of discontinuous surface topography, physical model construction, and laboratory direct shear experiment under different directions and normal stresses, was proposed to research the influence of discontinuity roughness on strength and deformation of discontinuity. During physical model construction of discontinuity, three types of discontinuity and rough natural rock joint surface models were constructed and moulded. Meanwhile, many influence factors of discontinuity surface topography, such as asperity inclination angle (AIA), asperity height (AH), normal stress (NS), and shear direction (SD), were considered during the direct shear experiment. On the basis of the experimental results, it can be found that there were two types of failure modes under different loading conditions, which were named "failure by shearing through the asperities" and "failure by sliding over the asperities". The obvious stress concentration phenomenon, climbing, and cutting effects appeared in the process of the direct shear experiment. In addition, the accurate identification of surface topography of natural rough rock joint surface was carried out using three-dimensional sensing system (3DSS) and self-programming software before and after the experiment. The subsamples with the same surface topography as the original samples were moulded using a self-developed instrument. Then, the mechanical behavior of the original samples and subsamples for the natural rough rock joint surface under different shear directions and normal stresses was studied. The results show that the shear displacement under different shear directions and normal stresses is very large before it reaches the failure state. And the residual strength of the original samples is higher than that of the subsamples. In addition, failure modes of the subsamples are main failure by shearing through the asperities due to the significant difference between peak shear strength and residual strength. The failure modes for parts of the original samples are failure by sliding over the asperities. The change ratio of area for the discontinuity after the experiment depends on surface topography, strength of heave on the surface of discontinuity, and particle size of minerals on the surface of discontinuity.